Development of a prototype for measuring plantar forces - Teodoro, Elaine Cristina Martinez [UNESP]; Tomazini, J. E. [UNESP]; Galera, S. R. G. P. [UNESP]; Nascimento, L. F. C. (My University, 2009)
Studies on the distribution of plantar pressure between the sole of the foot and the ground were developed before the 19th century. Currently, the most often employed plantar pressure measurement systems are Pedar® and FScan®, which have restrictions such as operational difficulty and high cost. In the present study, a device was constructed from two pressure plates capable of measuring plantar forces in discreet areas of the feet at a low cost, using strain-gages attached to sixteen strategic points of the mechanical elements. Sixteen prismatic beams were soldered to each frame, for which the free extremity of each beam represented a specific point of the foot. Two strain gauges were attached to each beam - one near the upper fixed extremity and the other near the lower fixed extremity. Using a Wheatstone bridge electric circuit, the gauges were used to measure the force acting on the extremity of the beam. Precision and accuracy of the prototype was about 10%. In some measurements, accuracy was 2%. The low precision and accuracy were mainly due to the restrictions of the available equipment, which only permitted four measurements at a time. Thus, it was necessary for participants to stand on the plates four separate times, which signified possible changes in the position of the feet on the pressure plates. Despite some limitations, the aim was achieved. The prototype has been used in some studies and represents a contribution to biomechanics, demonstrating the viability of using strain gauges.
Keywords: Plantar force; Podobarometry; Sensor; Strain-gauge; Electric circuit; High costs; Low costs; Mechanical elements; Plantar pressure measurement; Plantar pressures; Pressure plate; Prismatic beam; Strain gauge; Wheatstone bridges; Biomechanics; Biomedical engineering; Bridge circuits; Image processing; Imaging systems; Medical imaging; Pressure measurement; Sensors; Strain gages; Biophysics